Silicon vertex detector upgrade in the ALPHA experiment - Dirk van der Werf (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2013)
The Silicon Vertex Detector (SVD) is the main diagnostic tool in the ALPHA-experiment. It provides precise spatial and timing information of antiproton (antihydrogen) annihilation events (vertices), and most importantly, the SVD is capable of directly identifying and analysing single annihilation events, thereby forming the basis of ALPHA's analysis. This paper describes the ALPHA SVD and its upgrade, installed in the ALPHA's new neutral atom trap.